Ответы и объяснения

2013-05-18T16:38:10+00:00

  1) 3x+y=13  1) y= 13-3x         1) y= 13-3x  (2) 

2) xy=10       2) x(13-3x)=10  2) 13x-3x^2-10=0(1)

(1) 3x^2 - 13x +10=0

     D= 13^2 - 4 * 3 * 10= 49>0 => 2 k

x1= 13+k49/2*3= 20/6= 10/3 = 3целых 1/3

x2= 13-k49/2*3= 6/6= 1

(2) Если x =  3целых 1/3, то y = 13 - 3( 3целых 1/3 )= 13 - 10=3

Если x = 1 , то y= 13 - 3 *1 = 10

 

 

 

 

 

 

 

 

 

 

 

 

 

 

Лучший Ответ!
2013-05-18T23:32:22+00:00

3x+y=13

xy=10

 

3x+y=13

y=-3x+13

 

xy=10

x*(-3x+13)=10

-3x^2+13x-10=0

D=13^2-4*(-3)*(-10)=169-120=49

x1=(7-13)/(2*(-3))=1
x2=(-7-13)/(2*(-3))=10/3

 

3x+y=13

 

3*1+y=13

y1=10

 

3*(10/3)+y=13

10+y-13=0

y2=3